2013
DOI: 10.7814/jeen5v4p5zhk
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Beliefs of Entrepreneurship and Design Education: An Exploratory Study Comparing Entrepreneurship and Design Faculty

Abstract: Engineering capstone design and certain entrepreneurship courses have some similarities in terms of student outcomes, course structure, and instructional methods. Both types of courses have the tendency to be less structured than traditional courses and utilize teaching methods such as problem-based or project-based learning. The goals relating to the professional skill set are often similar and can include communication, writing, business, and team skills. Entrepreneurship instructors often focus on the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…The survey was constructed based on the results of a qualitative study 26 faculty interviews at three large research universities. The results of the qualitative study are available in Hochstedt, Zappe, and Kisenwether (2010) [3] and Zappe, Hochstedt, and Kisenwether (2012) [4].…”
Section: Faculty Surveymentioning
confidence: 99%
“…The survey was constructed based on the results of a qualitative study 26 faculty interviews at three large research universities. The results of the qualitative study are available in Hochstedt, Zappe, and Kisenwether (2010) [3] and Zappe, Hochstedt, and Kisenwether (2012) [4].…”
Section: Faculty Surveymentioning
confidence: 99%
“…14,15 Zappe, Hochstedt and Kisenwether conducted a study of faculty beliefs regarding entrepreneurship and design education. 16 One of their questions asked 37 entrepreneurship and capstone design faculty members to choose whether Entrepreneurship programs should "focus on: Intrapreneurship Only versus Entrepreneurship Only," or somewhere along a scale from zero (intrapreneurship only) to 100 (entrepreneurship only). An answer of 50 means "their responses tended to fall between Intrapreneurship Only and Entrepreneurship Only."…”
Section: Relevant Literaturementioning
confidence: 99%
“…An answer of 50 means "their responses tended to fall between Intrapreneurship Only and Entrepreneurship Only." 16 The median for entrepreneurship instructors was 60 (slightly skewed toward entrepreneurship only), while the capstone design instructors' medium response was 50. The range of responses for both groups was from 18 to 100, seeming to indicate that some faculty members held strong views regarding a clear distinction between what should be taught to educate entrepreneurs and intrapreneurs.…”
Section: Relevant Literaturementioning
confidence: 99%
“…3 In Atman's research, it was found that identifying the problem and its constraints, communicating, …and seeking information were among the most important design activities. 2 It is these concepts of design and technology commercialization that are often not explored enough in current semester-long design capstone classes and it was these concepts that were further explored by the students involved in the DeFINE Program.…”
Section: Introductionmentioning
confidence: 99%